2010
DOI: 10.1007/s11060-010-0395-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of O6-methylguanine DNA methyltransferase (MGMT) promoter methylation in patients with low-grade gliomas

Abstract: Methylation of the MGMT promoter is supposed to be a predictive and prognostic factor in glioblastoma. Whether MGMT promoter methylation correlates with tumor response to temozolomide in low-grade gliomas is less clear. Therefore, we analyzed MGMT promoter methylation by a quantitative methylation-specific PCR in 22 patients with histologically verified low-grade gliomas (WHO grade II) who were treated with temozolomide (TMZ) for tumor progression. Objective tumor response, toxicity, and LOH of microsatellite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Thirty-one studies (six in Asia, two in America and 23 in Europe) reported the effect of MGMT promoter methylation on OS using analyses adjusted for other factors. 23 , 26 30 , 33 42 , 45 , 68 , 75 , 77 , 82 91 , 93 As shown in Figure 4 , the HR of the Asian group is 0.56, the HR of the American group is 0.37 and the HR of the European group is 0.44; MGMT promoter methylation was significantly correlated with better OS according to multivariate analysis, with a combined HR of 0.44 (95% CI 0.38, 0.50). The random-effects model (the DerSimonian and Laird method) was used as significant heterogeneity was detected among these studies ( p = 0.000, I 2 = 50.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies (six in Asia, two in America and 23 in Europe) reported the effect of MGMT promoter methylation on OS using analyses adjusted for other factors. 23 , 26 30 , 33 42 , 45 , 68 , 75 , 77 , 82 91 , 93 As shown in Figure 4 , the HR of the Asian group is 0.56, the HR of the American group is 0.37 and the HR of the European group is 0.44; MGMT promoter methylation was significantly correlated with better OS according to multivariate analysis, with a combined HR of 0.44 (95% CI 0.38, 0.50). The random-effects model (the DerSimonian and Laird method) was used as significant heterogeneity was detected among these studies ( p = 0.000, I 2 = 50.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Very consistent results were also obtained by Dunn et al [34] in a cohort of 109 glioblastoma patients which were analysed by pyrosequencing. In addition, in a retrospective study of low-grade gliomas, we showed that the volumetric response to chemotherapy correlates with the level of MGMT-promoter methylation [38]. Single step or nested MSP gave rise to a mean overall survival of 10-12 months for patients with unmethylated MGMT promoter and 24-28 months for patients with methylated MGMT promoter (Electronic Supplementary Material, Figs.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to genetic diversity, it is becoming clear that when selective pressure is placed on MG, the high propensity for genetic mutation and redundant pathogenic mechanisms enable the rapid emergence of clones that are resistant to the applied pressure (58). Genetic instability and pathogenic redundancy are evidenced by the numerous DNA repair and methylation mechanisms that are commonly mutated in primary brain cancers, including the well-studied genes encoding p53 and O6-methylguanine methyltransferase (MGMT) (46, 52, 5861). An important example of the ramifications of genetic instability of glial tumors was observed in the Phase II trial of the EGFRvIII peptide vaccination.…”
Section: Challenges To Therapy For Infiltrating Brain Tumors – Definimentioning
confidence: 99%
“…Alternative fractionation schemes and techniques, including dose escalation, hyper- and hypo-fractionation, brachytherapy, charged particles, and radiosensitizing drugs, have been explored, but none have consistently demonstrated improvement in survival. Eventually a regional, fractionated radiation approach was found to be as effective as WBRT, providing a high dose to a more focused region while minimizing toxicity (61, 62). Currently, most patients with MG receive intensity modulated radiation therapy (IMRT) fractionated in daily doses of 2 Gy given 5 days per week for 6 weeks, for a total radiation dose of 60 Gy (5).…”
Section: Clinical Trials and The Standard Of Care: Successes Failurementioning
confidence: 99%